Analgesic requirements after major abdominal surgery are associated with OPRM1 gene polymorphism genotype and haplotype. (November 2008) - Hayashida, Masakazu; Nagashima, Makoto; Satoh, Yasuo; Katoh, Ryoji; Tagami, Megumi; Ide, Soichiro; Kasai, Shinya; Nishizawa, Daisuke; Ogai, Yasukazu; Hasegawa, Junko; Komatsu, Hiroshi; Sora, Ichiro; et al.
Aims: The association between SNPs of the human OPRM1 gene encoding the µµ-opioid receptor and postoperative analgesic requirements in surgical patients remains controversial. Here, we evaluate whether any of the five tag SNPs (A118G, IVS2+G691C, IVS3+G5953A, IVS3+A8449G and TAA+A2109G) representing the four linkage disequilibrium blocks of the OPRM1 gene influences postoperative analgesic requirements.Materials & methods: We studied 138 adult Japanese patients who underwent major open abdominal surgery under combined general and epidural anesthesia and received continuous postoperative epidural analgesia with opioids.Results: The 118G homozygous (GG) patients required 24-h postoperative analgesics more than 118A homozygous (AA) and heterozygous (AG) patients. Tag SNP haplotypes also were associated with 24-h postoperative analgesic requirements.Conclusions: These results suggest that OPRM1 gene tag SNP genotypes and haplotypes can primarily contribute to prediction of postoperative analgesic requirements in individual patients undergoing major open abdominal surgery.